2015
DOI: 10.1186/s12864-015-2039-6
|View full text |Cite
|
Sign up to set email alerts
|

In silico hybridization enables transcriptomic illumination of the nature and evolution of Myxozoa

Abstract: BackgroundThe Myxozoa, a group of oligocellular, obligate endoparasites, has long been poorly understood in an evolutionary context. Recent genome-level sequencing techniques such as RNA-seq have generated large amounts of myxozoan sequence data, providing valuable insight into their evolutionary history. However, sequences from host tissue contamination are present in next-generation sequencing reactions of myxozoan tissue, and differentiating between the two has been inadequately addressed. In order to shed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(58 citation statements)
references
References 54 publications
9
45
4
Order By: Relevance
“…Medusozoa encompasses the classes Staurozoa, Cubozoa, Scyphozoa, and Hydrozoa, whose phylogenetic relationships have been explored using morphology, life cycles, and nuclear and mitochondrial molecular markers (Marques & Collins, ; Collins et al ., ; Van Iten et al ., , ). Recently, some molecular phylogenetic analyses indicated that Myxozoa is a cnidarian group (Chang et al ., ; Foox & Siddall, ; Foox et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Medusozoa encompasses the classes Staurozoa, Cubozoa, Scyphozoa, and Hydrozoa, whose phylogenetic relationships have been explored using morphology, life cycles, and nuclear and mitochondrial molecular markers (Marques & Collins, ; Collins et al ., ; Van Iten et al ., , ). Recently, some molecular phylogenetic analyses indicated that Myxozoa is a cnidarian group (Chang et al ., ; Foox & Siddall, ; Foox et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Although low, our Busco scores were comparable to previously reported CEG scores for myxosporeans 15 . It is well known that myxozoan genomes and transcripts are AT-rich (> 60% AT), and AT content can be used to identify transcripts of parasite versus host origin 15,18,23,32 . The increased representation of non-AT-rich contigs in the intersect may, therefore, reflect the presence of non-parasite sequences (see later discussion) but it may also reflect the presence of myxozoan transcripts that encode proteins rich in amino acids using GC rich codons, such as minicollagens 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Non-parasite (< 60% AT) sequences were evident in the blob plots of both the fish kidneyderived and spore sac-derived transcriptomes. As highlighted by Foox and colleagues 23 , this illustrates the inadequacy of a single step depletion of host sequences by BLAST analysis against fish sequence resources. Notably the second peak in the blob plot of the spore sacderived transcriptome was not substantially reduced following filtering using a partial T. bryosalmonae genome assembly (H. Hartikainen pers comm).…”
Section: Bryosalmonaementioning
confidence: 96%
See 2 more Smart Citations